Параметри буропідривних робіт для проведення гірничих виробок - Кононенко, М.Н.; Хоменко, О.Є.; Коробка, Є.О. (Физико-технические проблемы горного производства, 2021)
Purpose. Development of a method for calculating the parameters of blasting works for mining, considering the physical and mechanical properties of rocks, energy characteristics of explosives (explosives), crack-mass of the massif and the action of rock pressure.
Methods. The paper uses a comprehensive methodological approach, which includes the development of methods for determining the parameters of the blasting works, considering the physical and mechanical properties of rocks and energy characteristics of explosives, fracture of the array and the action of rock pressure.
Findings. A new method of calculating the rational parameters of the blasting works during the preparatory workings was developed, which laid down the principle of placing groups of holes on the areas they occupy in the bottom of the workings and the location of holes on the jack contours.
Originality. The parameters of the location of boreholes in the bottom of the mine are realized according to the degree of change of the line of least resistance depending on the diameter of the borehole, physical and mechanical properties of the rock mass, energy characteristics of explosives and rock pressure.
Practical implications. The use of a new method of calculating the rational parameters of the blasting works for workings allows to save resources when performing tunneling work up to 18%. Мета. Розробка методики розрахунку параметрів буропідривних робіт (БПР) для проведення гірничих виробок з урахуванням фізико-механічних властивостей порід, енергетичних характеристик вибухових речовин (ВР), тріщинуватості масиву і дії гірського тиску.
Методика. У роботі використано комплексний методичний підхід, що включає розробку методики визначення параметрів БПР з урахуванням фізико-механічних властивостей порід та енергетичних характеристик ВР, тріщинуватості масиву та дії гірського тиску.
Результати. Розроблено нову методику розрахунку раціональних параметрів БПР при проведенні підготовчих виробок, в яку було закладено принцип розміщення груп шпурів за площами, які вони займають у вибою виробки та розташування шпурів за відбійними контурами.
Наукова новизна. Параметри розташування шпурів у вибої виробки реалізовано за степеневою закономірністю зміни лінії найменшого опору (ЛНО) у залежності від діаметру шпуру, фізико-механічних властивостей гірничого масиву, енергетичних характеристик ВР і дії гірського тиску.
Практична цінність. Використання нової методики розрахунку раціональних параметрів БПР для проведення виробок дозволяє здійснити ресурсозбереження при виконанні прохідницьких робіт до 18%. Цель. Разработка методики расчета параметров буровзрывных работ (БВР) для проведения горных выработок с учетом физико-механических свойств пород, энергетических характеристик взрывчатых веществ (ВВ), трещиноватости массива и действия горного давления.
Методика. В работе использован комплексный методический подход, включающий разработку методики определения параметров БВР с учетом физико-механических свойств пород и энергетических характеристик ВР, трещиноватости массива и действия горного давления.
Результаты. Разработана новая методика расчета рациональных параметров БВР при проведении подготовительных выработок, в которую был заложен принцип размещения групп шпуров по площадям, занимаемым в забоя выработки и расположения шпуров по отбойными контурами.
Научная новизна. Параметры расположения шпуров в забое выработки реализовано степенной закономерностью изменения линии наименьшего сопротивления (ЛНО) в зависимости от диаметра шпура, физико-механических свойств горного массива, энергетических характеристик ВР и действия горного давления.
Практическая ценность. Использование новой методики расчета рациональных параметров БВР для проведения выработок позволяет осуществить ресурсосбережения при выполнении проходческих работ до 18%.